Complexes of nickel(II) carboxylates with pyridine and cyclam: crystal structures, mesomorphisms, and thermoelectrical properties - Abdullah, N.; Said, S.M.; Halid, Y.Y.; Megat Hasnan, M.M.I.; Sharmin, N.; Mat Hussin, S.A.; Nik Ibrahim, N.M.J.; Nordin, A.R.; Safiin, N.A.; Anuar, N.S. (Taylor & Francis, 2016)
Nickel(II) carboxylates [Ni(CH3(CH2)14COO)2(H2O)2] (1) and [Ni(C6H5COO)2(H2O)2] (2) were obtained from reactions of NiCl2·6H2O with CH3(CH2)14COONa and C6H5COONa, respectively. Complex 1 reacted with pyridine (pyr) to form [Ni(CH3(CH2)14COO)2(pyr)2(H2O)2] (3) and [Ni2(μ2-H2O)(CH3(CH2)14COO)4(pyr)4] (4) in the same reaction mixture, and reacted with cyclam to form an ionic complex, [Ni(CH3(CH2)14COO)(cyclam)(H2O)]CH3(CH2)14COO·4H2O (5). In contrast, 2 reacted with cyclam to form [Ni(C6H5COO)2(cyclam)] (6). Finally, 6 reacted with p-(hexadecyloxy)pyridine (L) to form an ionic complex, [Ni(cyclam)(L)2](C6H5COO)2 (7). Complexes 3–6 were single crystals. All complexes have octahedral Ni(II) center(s) and were magnetic. Complexes with cyclam as co-ligand were more thermally stable than those with pyridine and its derivative, L. Complexes 3 and 4 were mesomorphic after partial loss of water and/or pyridine ligands on heating. The ionic complexes 5 and 7 were not mesomorphic, but showed good thermoelectrical behavior with negative Se values in CHCl3 (−0.28 mV K−1 for 5; -0.39 mV K−1 for 7) and positive Se values in C2H5OH (+0.25 mV K−1 for 5; +0.20 mV K−1 for 7).